2020
DOI: 10.3390/ani10010130
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Toxin Effects of β-Zearalenol and HT-2 on Bovine Granulosa Cells Using iTRAQ-Based Proteomics

Abstract: Zearalenone (ZEA) and T-2 are the most common mycotoxins in grains and can enter the animal and human food-chain and cause many health disorders. To elucidate the toxic response profile, we stimulated bovine granulosa cells (GCs) with β-zearalenol or HT-2. Using isobaric tags for relative and absolute quantification (iTRAQ)-based proteomic, 178 and 291 differentially expressed proteins (DEPs, fold change ≥ 1.3 and p-value < 0.05) in β-zearalenol and HT-2 groups were identified, respectively. Among these DEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Bovine granulosa cells were exposed in vitro to 0.09 and 3.1 µM α-ZEL and presented a decrease in the synthesis of estradiol and progesterone, respectively, whereas exposure to β-ZEL at the same concentrations did not affect cell function [169]. At a higher concentration of 25 µM, β-ZEL was able to induce endoplasmic stress in granulosa cells with a subsequent decrease in the estradiol secretion [185]. These authors observed a similar behavior when bovine granulosa cells were exposed to 50 nM HT-2 toxin, the metabolite from the T-2 toxin.…”
Section: In Vitro Experimental Trialsmentioning
confidence: 98%
See 2 more Smart Citations
“…Bovine granulosa cells were exposed in vitro to 0.09 and 3.1 µM α-ZEL and presented a decrease in the synthesis of estradiol and progesterone, respectively, whereas exposure to β-ZEL at the same concentrations did not affect cell function [169]. At a higher concentration of 25 µM, β-ZEL was able to induce endoplasmic stress in granulosa cells with a subsequent decrease in the estradiol secretion [185]. These authors observed a similar behavior when bovine granulosa cells were exposed to 50 nM HT-2 toxin, the metabolite from the T-2 toxin.…”
Section: In Vitro Experimental Trialsmentioning
confidence: 98%
“…Granulosa cells are used as species-specific models to evaluate the effects of toxins on steroidogenesis, oxidative stress, and apoptosis. In cattle, most cells are collected from small ovarian follicles (1-7 mm) [169,185,186], whereas one study was performed with granulosa cells harvested from large follicles (8-22 mm) [187]. It was noteworthy that granulosa cells from large follicles are less sensitive to mycotoxin exposure than those from small follicles.…”
Section: In Vitro Experimental Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second purpose of the present study was to evaluate both ZEN (Fusarium mycotoxin called pre-harvest mycotoxin) and STC (Aspergillus mycotoxin called post-harvest mycotoxin) dynamics in the dietary roughage (rice straw and WCS) using the naturally ZEN (also STC)-contaminated herd (Herd C) detected in August 2019 as a model/examined herd, mainly by urinary ZEN monitoring during the year from July 2020 to June 2021. In addition, ZEN and its metabolites have been suggested to cause apoptosis of granulosa cell/atresia of follicles in several animals [27][28][29][30], the relationship between urinary ZEN and AMH concentration during the monitoring period was studied to clarify the effects of ZEN exposure on AMH secretion from antral follicles. In this regard, similar to our recently reported decrease in AMH concentration during the peripartum period [19], all five examined JB cows displayed a clear decline in AMH concentrations in the month of their calving with a large range of SAA concentrations (Cow 1: 3.1 mg/L, Cow 2: 23.4 mg/L, Cow 3: 4.9 mg/L, and Cow 5: 2.9 mg/L; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Of the genes that have possibly undergone parallel selection in both the native and invasive range, we see a number of these genes which have been previously associated with responses to various pollutants. Exposure to HT-2, a grain mycotoxin, has been shown to downregulate nidogen 2 (NID2) expression in bovines (Li et al 2020a). Starling interaction with livestock is well documented, and indeed is a key motivating factor of their management in agricultural areas (Linz et al 2007).…”
Section: Genes Undergoing Putative Adaptive Selectionmentioning
confidence: 99%